2020
DOI: 10.1080/09537287.2020.1834135
|View full text |Cite
|
Sign up to set email alerts
|

Operational excellence in humanitarian logistics and supply chain management through leagile framework: a case study from a non-mature economy

Abstract: Past few years have continuously seen an increase in intensity and frequency of climate-related disasters in non-mature economies. Most of these losses can be attributed to inefficient and ineffective management of humanitarian logistics and supply chains during the preparedness, response and reconstruction phases of disaster relief operations. Previous researches have focussed primarily either on the response phase of humanitarian logistics or on the humanitarian supply chain coordination issues mostly within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Similarly, the International Federation of Red Cross and Red Crescent Societies (IFRC) defines disaster as a sudden event that seriously disrupts society's functioning with loss of human life and resources beyond the ability to recover [20]. HSCM intends to meet the affected people's needs by efficiently using the given resources during and after the disaster [21]. Additionally, HSCM seeks to mitigate the suffering of the affected population to the fullest extent possible.…”
Section: Sustainable Humanitarian Supply Chain Management (Shscm)mentioning
confidence: 99%
“…Similarly, the International Federation of Red Cross and Red Crescent Societies (IFRC) defines disaster as a sudden event that seriously disrupts society's functioning with loss of human life and resources beyond the ability to recover [20]. HSCM intends to meet the affected people's needs by efficiently using the given resources during and after the disaster [21]. Additionally, HSCM seeks to mitigate the suffering of the affected population to the fullest extent possible.…”
Section: Sustainable Humanitarian Supply Chain Management (Shscm)mentioning
confidence: 99%
“…Humanitarian aid is needed across all the four disaster management stages of preparedness, mitigation, response, and recovery [3] and therefore, humanitarian supply chains (HSCs) deliver the aid in form of goods (food, water, medical supplies, shelter) and services to the victims. HSC studies the management of disaster operations across all the four stages and it includes the processes of material sourcing, procurement, transportation, storage, and timely delivery to the victims to diminish deaths, resources, and assets losses [4].…”
Section: Introductionmentioning
confidence: 99%
“…Information sharing gaps exists amongst partners and if effective communication is enhanced, that would improve collaboration, enhanced transparency, and efficiency of operations [6]. The governance of HSCs is characterised by centralised decision making that is time consuming and uncoordinated thus, clarity in accountability is minimal [4], which could lead to fraud and corruption of humanitarian aid [7]. Several authors have suggested that blockchain technology (BCT) in HSCs would help to minimise these challenges [8]; [9], thus leading to more efficient outcomes, but the development and implementation of BCT in HSCs are still young.…”
Section: Introductionmentioning
confidence: 99%
“…Nayaka discussed the application of a comprehensive streamlining framework in the humanitarian supply chain. The research results emphasized that efficient humanitarian supply chain management is inseparable from the need to have precise logistics [39].…”
Section: Identification Of Criteria and Indicatorsmentioning
confidence: 99%